(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
ملخص: تناولت الدراسة العلاقة الدينامكية والسببية لأثر الشفافية في القطاع العام على إستقطاب الإستثمار الأجنبي المباشر وذلك من خلال تحليل بيانات (Penal)، باستخدام برنامج Eviews10، وخلصت الدراسة إلى أن هناك علاقة سببية موجبة في اتجاه واحد من الشفافية في القطاع العام نحو الاستثمار الأجنبي المباشر، وهو ما أظهره كذلك معامل الارتباط الذي بلغ 52.5% ، كما بينت الدراسة الدينامكية لنموذج (var) ونتائج تحليل التباين أن إستجابة معدل الإستثمار الأجنبي لصدمات الشفافية في القطاع العام له أثار إيجابية في المدى القصير والمتوسط وحتى الطويل. الكلمات الدالة: الشفافية في القطاع العام، الإستثمار الأجنبي المباشر، بيانات البنال، نموذج شعاع الإنحدار الذاتي. Abstract: The study examined the dynamic and causal relationship of the effect of transparency in the public sector on attracting foreign direct investment polarization through penal data analysis, using the Eviews10. The study concluded that there is a positive causal relationship in one direction of transparency in the public sector toward foreign direct investment, which was also shown by the 52.5% correlation coefficient. The dynamic study of the VAR model and the variance decomposition results also showed that the response of the foreign investment rate to transparency shocks in the public sector has positive effects in the short, medium and even long term. Key words: Transparency in the public sector, foreign direct investment, Penal data, Autonomous Beam Model.